2021
DOI: 10.1177/00034894211037414
|View full text |Cite
|
Sign up to set email alerts
|

Response of Laryngopharyngeal Symptoms to Transoral Incisionless Fundoplication in Patients with Refractory Proven Gastroesophageal Reflux

Abstract: Objective: Patients with laryngopharyngeal reflux (LPR) symptoms may not respond to proton pump inhibitors (PPI) if they have an alternative laryngeal diagnosis or high-volume reflux. Transoral incisionless fundoplication (TIF) or TIF with concomitant hiatal hernia repair (cTIF) are effective in decreasing symptoms of gastroesophageal reflux disease (GERD) but are not well studied in patients with LPR symptoms. This prospective multicenter study assessed the patient-reported and clinical outcomes after TIF/cTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…8 Further, because of the limitations of clinical tools, many symptoms and extrapharyngeal manifestations were not considered. 9 Although knowledge on nonacidic LPR has recently progressed, a treatment plan based on PPIs has not been developed. 2 The therapeutic effect of PPIs alone to inhibit acid reflux is not ideal and therefore has also been evaluated incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…8 Further, because of the limitations of clinical tools, many symptoms and extrapharyngeal manifestations were not considered. 9 Although knowledge on nonacidic LPR has recently progressed, a treatment plan based on PPIs has not been developed. 2 The therapeutic effect of PPIs alone to inhibit acid reflux is not ideal and therefore has also been evaluated incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…At a median of 14 months follow‐up, RSI score decreased from 19.2 to 6.1 after TIF ( p < 0.001). Snow et al 137 similarly showed in 49 patients with refractory LPR symptoms (RSI > 13) and either erosive oesophagitis, Barrett's oesophagus and/or pathological acid reflux undergoing TIF or TIF with hiatal hernia repair, 85% had normalisation of their RSI post‐procedure.…”
Section: An Overarching Perspective On Goals Of Managementmentioning
confidence: 95%
“…In 2017, FDA allowed modification of the TIF device instructions for use, permitting TIF to be performed with hiatal hernia repair, similar to surgical fundoplication. There is growing evidence of the safety and efficacy of cTIF procedures for typical and atypical GERD symptoms [26 ▪ ,32–34]. A recent study by Jaruvongvanich et al compared hiatal hernia repair followed by LNF to cTIF and showed comparable results between the two groups for postprocedural PPI use, dysphagia, esophagitis, disrupted wrap, and hiatal hernia recurrence.…”
Section: Introductionmentioning
confidence: 99%